MEMBANGUN MODEL DINAMIS PENANGKARAN POPULASI MALEO (Macrochepalon Maleo) YANG MEMPERTAHANKAN EKSISTENSINYA DARI PREDATOR - Gusmawan, T; Ratianingsih, R; Nacong, N (Program Studi Matematika, Universitas Tadulako, 2018)
Maleo (Macrocephalon maleo) is one of the endangered endemic species of Sulawesi due to diminishing spawning habitat, community exploitation and predators. The dynamic model of maleo population captivity to conserve its existence from predators is a mathematical model that describes the dynamics of maleo population growth cycle (M) with the threat of predators (P). In this study, the population of eggs maleo divided into two groups that are eggs in the free zone (Tb) and eggs in breeding (Tp). The eggs are in the captive breeding will be transfered to the exposure group (E). The model represents the interaction between the predators and populations reflecting maleo in each growth phase. The model has two critical points, namely the critical point ð‘‡1 = ( 0,0,0,0, ðœ‘ Âµ2 ) describing maleo extinction condition and critical point ð‘‡2 = (ð‘€âˆ— , ð‘‡ð‘âˆ— ,ð¸ âˆ— , ð‘‡ð‘âˆ— , ð‘ƒ âˆ— ) which describes the endemic conditions of maleo growth dynamics. The stability analysis shows that the system is unstable at both critical points. It is because the values of the first column in the Routh Hurwitz table changes in sign. Simulations of the endemic conditions showed that the maleo and egg populations in the free zone are decreasing with respect to time even though the exposed maleo still exist. The unstable endemic indicates that the existence of maleo breeding program in conservation areas still need another efforts support.